Sosialisasi Pengenalan Lubang Resapan Biopori untuk Kelompok Tani di Desa Kesambi, Kecamatan Pucuk, Kabupaten Lamongan (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2026)
The utilization of biopore infiltration holes has become one of the simple and effective innovations in environmental management and soil resource conservation, with great potential to support a healthy environment. This community service activity aims to enhance farmers' understanding of the use of biopore infiltration holes as an effort for soil and water conservation as well as sustainable organic waste management. The outreach was conducted on September 7, 2024, at the Kesambi Village Hall, Pucuk District, Lamongan Regency, targeting 12 members of the farmer group. The implementation method of the activity included preparation stages, conducting a pretest, delivering material along with interactive discussions, and concluding with a posttest as an evaluation of the participants' understanding improvement. The results of the activity indicate an increase in the average knowledge score of participants from 81.25 in the pretest to 97.92 in the posttest. This demonstrates that the socialization method applied was effective in enhancing farmers' understanding of the functions, production techniques, and benefits of biopores. This activity is expected to encourage the independent implementation of biopores by farmer groups, both at the household and agricultural levels, as part of environmentally friendly and sustainable land management practices.